The Effects of Poultry Farming on the Socio-Economic Development of Women in Rural Areas: A Case of Bichi Local Government Area of Kano State, Nigeria - Sanusi, Nassarawa Isma'il (NIU Journal of Humanities, 2018)
The paper is all about the impact of smallholder farmerâ€™s production of local chicken on economic development of Nigeria basing on the case study of Bichi Local Government of Kano State in Nigeria. The specific objectives of the study which are to identify the challenges faced by farmers in conducting the activity of chicken production and to provide a solution  to the challenges faced by poultry farming on socio-economic development in Bichi Local Government of Kano State in Nigeria. The paper applied a descriptive research design in the study to ensure effective collection of data from the respondents. During sample procedures, the researcher selected 120 people who were considered as respondents and these were categorized as follows; 60 Farmers, 40 Business people and 20 were Agricultural officials who are conducting their businesses and stay in the area of Bichi Local Government of Kano State in Nigeria. Both Purposive sampling and simple random sampling techniques were applied during data collection in acquiring data from the participants, Data instruments used includes Questionnaires, Observations and Interview guide, in doing so, the researcher drafted questions which were distributed to the respondents to fill in their opinions and consents about the study. Data analysis was done using statistical package for social sciences and Microsoft excel as data packages in processing and analysis of data collected from the respondents. Findings from responses shows that several challenges affecting local chicken production where identified such as inadequate resources, diseases, lack of expertise, poor markets among others were identified during data collection.  Keywords: Poultry farming, Local chicken, Chicken Production.